Toward social criteria and indicators for protected areas: one cut on adaptive co-management - Colfer, C.J.P.; Prabhu, Ravi; Wollenberg, Eva Karoline; McDougall, C.; Edmunds, D.; Kowero, G.S. (CRC Press, 2001)
This chapter summarizes CIFOR’s work on social criteria and indicators (C&I), developed within commercial establishments oriented toward timber harvesting. These C&I are then examined from the point of view of protected areas, based on Colfer’s experience managing an Indonesian wildlife reserve in 1992-93. The conclusion is that almost all of the social C&I are equally applicable to protected areas, with only slight changes in wording.